Service Quality Analysis to Increase Customer Satisfaction at Hypermart Supermarket - Prisetyo, Berlin Sippy; Juwono, Marvella; Robert, Verencia (Journal of Current Research In Multidisciplinary, 2023)
The research aims to find solutions for how supermarkets can improve the quality of their services. In this study, there were 10 attributes used in the Google form to be distributed to 30 respondents who had visited and shopped at supermarkets. From the GAP analysis, the indicator with the smallest value is Q4 with a GAP of -0.300, followed by Q6, Q9, Q5, Q3, Q8, Q2, Q7, Q10, and Q1 with the greatest value. And what the company needs to pay attention to and improve are the 4th, 6th, 9th, 5th, and 3rd indicators. It is these five indicators that require changes to reduce the level of disparity between other indicators. The results of the analysis of supermarket service quality research obtained are: Q4, Q5, and Q9 are included in quadrant 1, which means that according to consumers, these indicators are important indicators, but in supermarkets, their performance is still poor. There are no indicators in quadrant 2. Q2, Q3, Q6, Q7, Q8, and Q10 are included in quadrant 3, which means that according to consumers, these indicators are not important, and after consumers experience these indicators in their daily lives, it turns out that these indicators are also not good. Q1 is included in quadrant 4, meaning that according to consumers, this indicator is not important, but supermarkets have performed well so that they are sometimes considered excessive by consumers.